From amoeboid myosin to unique targeted medicines for a genetic cardiac disease - Spudich, James A. (Frontiers in Physiology, 2024)
The importance of fundamental basic research in the quest for much needed clinical treatments is a story that constantly must be retold. Funding of basic science in the USA by the National Institutes of Health and other agencies is provided under the assumption that fundamental research eventually will lead to improvements in health care worldwide. Understanding how basic research is connected to clinical developments is important, but just part of the story. Many basic science discoveries never see the light of day in a clinical setting because academic scientists are not interested in or do not have the inclination and/or support for entering the world of biotechnology. Even if the interest and inclination are there, often the unknowns about how to enter that world inhibit taking the initial step. Young investigators often ask me how I incorporated biotech opportunities into my otherwise purely academic research endeavors. Here I tell the story of the foundational basic science and early events of my career that led to forming the biotech companies responsible for the development of unique cardiac drugs, including mavacamten, a first in class human β-cardiac myosin inhibitor that is changing the lives of hypertrophic cardiomyopathy patients.